The role of fecal microbiota transplantation on the NLRP3-Caspase 1 pathway and anxiety like behavioral in the ulcerative colitis model in rats - Mohammad Mohammadi; Kaveh Rahimi; Anahita Rezaie; Mohammad Reza Tabandeh (Scientific Reports)
Abstract The purpose of this study was to investigate the function of the NLRP3-Caspase 1 signaling pathway in the colon during fecal microbiota transplantation (FMT) in colitis induced by acetic acid. Additionally, the study aimed to determine the impact of FMT on anxiety behaviors by analyzing the function of the NLRP3-Caspase 1 signaling pathway in the hippocampus. A total of twenty-four rats were selected randomly for the study and divided into two groups, a control group, and an acid acetic-induced colitis group. The acid acetic-induced colitis group further consisted of three subgroups: untreated acid acetic-induced colitis group, mesalazine 0.3 gr/kg group, and FMT group. After 6 days, the colon was evaluated for macroscopic and microscopic damage, and the signaling pathway NLRP3-Caspase1-related genes in the colon and hippocampus were analyzed. Additionally, anxiety-related behaviors of the rats were observed. FMT decreased colonic mRNA expression levels of NLRP3, NF-кB, and Caspase1 and pro-inflammatory cytokines (IL-1β and IL-18). Also, FMT reduced the expression of NLRP3, NF-κB, and Caspase1 protein levels as well as pro-inflammatory cytokines IL-1β and IL-18 in the hippocampus, resulting in a reduction of anxiety behaviors in the open field and elevated plus maze tests in the colitis model. FMT may improve acetic acid-induced colitis by regulating the NLRP3-Caspase1 signaling pathway in the colon. It also reduced colitis-induced anxiety behavior by regulating the expression of proteins related to the NLRP3-Caspase 1 pathway in the hippocampus.